2019
DOI: 10.1002/ejoc.201901547
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Asymmetric Transfer Hydrogenation with Long Catalyst Lifetime and Low Metal Leaching

Abstract: Homogenous iridium complexes with asymmetric ligands and different tether lengths have been solid‐supported and prepared in multi‐gram quantities. Packed in a fixed‐bed, they have been used in continuous flow for up to 120 hours in the asymmetric transfer hydrogenation of APs in 2‐propanol to make 1‐phenethyl alcohols in > 95 % conversion and ee. The CsDPEN ligand and C5 tether showed higher performance than TsDPEN and the C14 tether, whilst the ketone feed concentration and reaction temperature were optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The main benefits are that its geometry allows uniform distribution of gas and liquid, which facilitates the gas interaction in the reaction system as explained in-depth by Shah et al In flooded bed operation a liquid phase and gas phase, flow cocurrently upward over the catalyst bed (3-phases) or a liquid flows up over the catalyst bed (2-phases), for example, transfer hydrogenation flows up over the catalyst bed. ,, In flooded bed operation, the main benefits are that complete wetting of the catalyst surface is achieved and compression of the bed within the reactor is avoided, thereby avoiding high pressure drops, allowing catalysts with a smaller particle size to be used. The Dow chemical company have compared a catalyst bed diluted with fines in trickle bed and flooded bed mode to evaluate wetting of the catalyst bed following the work of Wu et al and Chander et al In addition, Pitault et al comments on the comparison of particle size in trickle bed and flooded bed mode . There are numerous reports in the literature of flooded bed heterogeneous transfer hydrogenations (fixed bed transfer hydrogenation); for example, Ono Pharmaceutical Co., Ltd., have demonstrated the use of a fixed bed reactor for an asymmetric transfer hydrogenation of a range of substituted benzophenones, Scheme a: 4a – g to 1-phenethyl alcohols in >95% enantiomeric excess ( ee ) 5a – g . Novartis have demonstrated the use of a fixed bed reactor in flooded bed mode gas/liquid up flow for the reduction of N -4-nitrophenyl nicotinamide 6 (model system) to the primary amine 7 Scheme b …”
Section: Continuous Flow Hydrogenation Technologiesmentioning
confidence: 99%
“…The main benefits are that its geometry allows uniform distribution of gas and liquid, which facilitates the gas interaction in the reaction system as explained in-depth by Shah et al In flooded bed operation a liquid phase and gas phase, flow cocurrently upward over the catalyst bed (3-phases) or a liquid flows up over the catalyst bed (2-phases), for example, transfer hydrogenation flows up over the catalyst bed. ,, In flooded bed operation, the main benefits are that complete wetting of the catalyst surface is achieved and compression of the bed within the reactor is avoided, thereby avoiding high pressure drops, allowing catalysts with a smaller particle size to be used. The Dow chemical company have compared a catalyst bed diluted with fines in trickle bed and flooded bed mode to evaluate wetting of the catalyst bed following the work of Wu et al and Chander et al In addition, Pitault et al comments on the comparison of particle size in trickle bed and flooded bed mode . There are numerous reports in the literature of flooded bed heterogeneous transfer hydrogenations (fixed bed transfer hydrogenation); for example, Ono Pharmaceutical Co., Ltd., have demonstrated the use of a fixed bed reactor for an asymmetric transfer hydrogenation of a range of substituted benzophenones, Scheme a: 4a – g to 1-phenethyl alcohols in >95% enantiomeric excess ( ee ) 5a – g . Novartis have demonstrated the use of a fixed bed reactor in flooded bed mode gas/liquid up flow for the reduction of N -4-nitrophenyl nicotinamide 6 (model system) to the primary amine 7 Scheme b …”
Section: Continuous Flow Hydrogenation Technologiesmentioning
confidence: 99%
“…Catalysts and intermediates 1−5 were prepared using published procedures. 33 Synthesis of Amines. Racemic α-methylbenzylamine 6, (S)-αmethylbenzylamine (S)-6, racemic N,N-dimethyl-α-methylbenzylamine 9, (S)-N,N-dimethyl-α-methylbenzylamine (S)-9, (R)-N,Ndimethyl-α-methylbenzylamine (R)-9, racemic 2-methylpiperidine 11, and (S)-2-Methylpiperidine (S)-11 were bought from Sigma-Aldrich Ltd. (1S,4S)-N-Methyl-4-(3,4-dichloro)phenyl-1-amino-1,2,3,4-tetrahydronaphthalene 12 was received as a gift from S.Amit and Co. India Ltd.…”
Section: = ×mentioning
confidence: 99%
“…Similarly, a polymer supported chloro-iridium catalyst, tethered by a functionalized Cp* ligand, is reported for the reduction of benzaldehyde and repeated reuse . The same supported metal, modified with chiral ligand, has shown a long lifetime in the continuous flow asymmetric transfer hydrogenation of ketones …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using alcohol instead of hydrogen as hydrogen source is an ideal method. Blacker and co‐workers demonstrated that different Ir‐based catalysts had good activity in the asymmetric transfer hydrogenations . A series of homogeneous and heterogeneous Ir‐based catalysts were used in the asymmetric hydrogenation of a model compound, that is, phenyl acetyl.…”
Section: Continuous‐flow Hydrogenation Using Heterogeneous Catalystsmentioning
confidence: 99%